Divine Parody: Ridiculing America’s Spiritual Crisis in Neil Gaiman’s American Gods - Ahmad Wildan Rizaq; Eka Nurcahyani (Journal of Language and Literature, 2022)
One of the reasons for modern man's mental disorders is a spiritual crisis. In American Gods, Neil Gaiman ridicules this condition by reviving religious, folklore, and mythological entities into new contexts. These entities, however, are simplified as merely intertextual references by most studies. In fact, the new contexts are pragmatically intended to parody American modernity in leading modern man to a spiritual crisis. This research, thus, aims to be a descriptive-analytical study that not only interprets such references through intertextual analysis but also uses pragmatic analysis to examine how the novel parodically portrays modern man's spiritual journey. Deploying Linda Hutcheon's Interpretation of Parody, the Intertextual analysis results that these mythological characters are resituated to represent marginal communities, like ex-convicts, fugitives, drifters, gangsters, immigrants, homeless, laborers, prostitutes, and relocators. While applying Jung's interpretation of the relationship between mythological archetypes and psychological traits, the pragmatic analysis suggests that the hero archetype has been reimagined to caricature modern man's spiritual journey in reconciling his conscious desire with unconscious competencies that resulting disorders in his mental. The factors that influence the hero's mental stability are manifested through the trickster characters in deceiving the hero's consciousness with secular realities, while the sage characters reinforce the hero's unconsciousness through some spiritual journeys.